Effect of adding lay-tutors to the educational part of a back school programme for patients with subacute, non-specific low back pain: A randomized controlled clinical trial with a two-year follow-up - Inge Grundt Larsen; Lisa Gregersen Oestergaard; Lene M. Thomsen; Claus Vinther Nielsen; Berit Schiøttz-Christensen (Medical Journals Sweden, 2019)
Objective: To evaluate the effect of adding a lay-tutor to the educational sessions of a back school programme for patients with subacute low back pain. Methods: Patients with subacute low back pain were randomized to a 10-week programme comprising 10 h education and 20 h physical exercise led by a former patient as lay-tutor, or a programme led by a physiotherapist. In the intervention group, former patients served as lay-tutors in the educational sessions, teaching in conjunction with physiotherapists. In the control group, 2 physiotherapists led the entire educational programme. Disability, back pain, leg pain and health status were evaluated blindly at 3 and 24 months. Results: Eighty-seven patients with subacute low back pain referred for treatment at 6 selected physiotherapy clinics were allocated to either an intervention group (n = 42) or a control group (n = 45). No statistically significant difference was found between the 2 groups. Both groups of patients showed a statistically significant improvement in health and pain measurements from the start of the study to the 3- and 24-month follow-up. Conclusion: No short- or long-term effect was found of adding a lay-tutor to the educational sessions of a back school programme for patients with subacute low back pain with regards to functional activity, back pain, leg pain or general health. The main limitations are that the potential effect of including lay-tutors in the educational part of a back school programme as an intervention in itself has to be tested, and the programme has to be tested as a complete protocol. Also, no specific testing has been performed to confirm the ideal number of sessions in the programme.